1993
DOI: 10.1089/neu.1993.10.73
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nimodipine on High-Energy Phosphates and Intracellular pH During Cerebral Ischemia

Abstract: Experimental and clinical studies suggest that the calcium channel blocker nimodipine may reduce cerebral ischemic injury. Using rapid acquisition phosphorus-31 nuclear magnetic resonance (31P NMR) spectroscopy, we examined the effect of nimodipine on cerebral energy metabolism during severe ischemia in gerbils. High-energy phosphates and intracellular pH were characterized at baseline and at 2-min intervals following bilateral common carotid artery (CCA) ligation. Serial forebrain spectroscopy was continued u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Under pathological conditions there is some evidence for direct interactions between CCB and phosphorus metabolism, but they are scarce. For instance, the protective effect of CCB against ischaemic damage has been associated with delayed cellular depletion of high-energy phosphate, be it in the brain with nimodipine [16], in the myocardium with nifedipine [17] and verapamil [ 18] or in the kidney with verapamil [19]. Such intracellular accumulations of phosphorus could not account for increments in plasma levels as observed with diltiazem, but could theoretically be invoked to decrements in plasma phosphorus levels * Data on phosphorus were not reported in the paper.…”
Section: Discussionmentioning
confidence: 99%
“…Under pathological conditions there is some evidence for direct interactions between CCB and phosphorus metabolism, but they are scarce. For instance, the protective effect of CCB against ischaemic damage has been associated with delayed cellular depletion of high-energy phosphate, be it in the brain with nimodipine [16], in the myocardium with nifedipine [17] and verapamil [ 18] or in the kidney with verapamil [19]. Such intracellular accumulations of phosphorus could not account for increments in plasma levels as observed with diltiazem, but could theoretically be invoked to decrements in plasma phosphorus levels * Data on phosphorus were not reported in the paper.…”
Section: Discussionmentioning
confidence: 99%
“…During liver ischemia, the deficit of metabolic subAlthough extensive studies on calcium channel strates induces important biochemical changes such as blockers agree that there is a beneficial effect on ischdegradation of ATP and other energetic metabolites: emia and reperfusion, the literature is rather contraactivation of enzyme systems, phospholipases, and prodictory concerning the explanation of mechanisms of teases that may lead to damage of the cell membrane action of these drugs. In central nervous system ischthrough production of oxygen-reactive species, hydrolyemia, Lemons et al [36] showed that, in gerbils, nimodsis of phospholipids, membrane blebbing, and cell lysis ipine in high doses slowed the depletion of high-energy [1]. Lack of oxygen and cellular energy depletion lead phosphates (measured by phosphorus 31 nuclear magto abnormal balance of intracellular metabolites and netic resonance).…”
Section: Histological Findingsmentioning
confidence: 99%